What happens when you heat nicotine molecule in different atmospheres – a molecular modelling perspective - Mereme I.; Achevski, Blagoj; Godzo H.; Tonikj ribarska, Jasmina; Pejov L. (5th Scientific Summit Tobacco Harm Reduction: Novel products, research and policy, 21 – 22 September 2022, Athens, Greece (Abstract book, poster presentation), 2022)
The fate of nicotine molecule, when heated at different temperatures in different surroundings (i.e. atmospheres) is of fundamental importance to harm reduction when inhaling the aerosols of different tobacco products. In the present study, we tackle this issue from the viewpoint of molecular modelling. Series of ab initio molecular dynamics simulations of free nicotine molecule as well as of nicotine molecule in the presence of oxygen molecules at series of different temperatures ranging from 600 to 1200 K are performed with the atom-centered density matrix propagation scheme (ADMP). Simulations are performed at different levels of theory. The possible degradation pathways implied by the generated molecular dynamics trajectories are related to the products detected in the smoke of conventional cigarettes and aerosols generated by electronic devices for controlled heating of tobacco.